Is the scrum board feminine? - Sauer, Stefan; Tihlarik, Amelie (The Gender of Things, 2023)
The Scrum board plays a vital role in empowering team-based work: agile teams use it to discuss, plan, and estimate their tasks and coordinate these on a daily basis as required. This chapter examines whether the Scrum board can be seen as a feminine tool. Is it a tool by means of which female empowerment is or can be materialized? Does it contribute to creating more gender equity in the world of work? In pursuing these questions, aspects of technocentrism, hierarchies, cooperation and emotions, and bureaucracy are analysed in the light of previous feminist research on the Scrum board, as well as the Agile Manifesto and its approach<br
CRIS-Team Scopus Importer:2024-12-16